Non-Belief and Hostility: Exploring Atheism and Anti-Islam Sentiment - Hassan, Sharif Ratul (Journal of Modern Islamic Studies and Civilization, 2026)
This study explores the nuanced relationship between atheism and anti-Islam sentiment in Muslim-majority contexts. Drawing principally on qualitative research augmented by quantitative data, it brings together textual and legal analysis, statistical evidence, and in-depth case studies. The research adopts a neutral perspective, aiming to present atheist worldviews, which emphasize reason, evidence, and scientific inquiry rather than religious belief, in an objective manner. It distinguishes atheism, defined as the lack of belief in God or gods, from anti-Islam sentiment, which involves prejudice, hostility, or opposition toward Islam and its followers. The findings show that atheism exists in Muslim-majority regions, including Iran, Turkey, and parts of the Arab world. It further identifies historical and contemporary controversies, such as the Rangila Rasool case, the Danish cartoons, and Quran desecrations, which reveal that blasphemous acts frequently provoke vigorous social, political, and legal responses. The study also examines strict blasphemy laws in countries like Pakistan, Jordan, and Indonesia, highlighting tensions between freedom of thought and religious protection.